Islamic Symbols in Europe: the European Court of Human Rights and the European Institutions (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione nel volume, a cura di   R. Scarciglia, Islamic Symbols in European Courts,Quaderni giuridici del Dipartimento di Scienze politiche e sociali, Cedam – Kluwer, Trieste, 2014SUMMARY: 1. Preliminary Remarks - 2. The veil before the European Court of Human Rights – 3. Religious Symbols in Article 9 ECHR case law and women’s religious freedom in Europe – 4. Islamic Symbols and European Institutions. Indirect Discrimination? – 5. Conclusive Remarks. AbstractReligious freedom within Europe and the place of Islam within Europe are of particular contemporary interest. The focus of recent case law developed by the European Court of Human Rights (ECtHR) has been on national laws which proscribe the wearing of religious symbols in certain aspects of the public sphere, and on the claims more generally to religious and cultural freedom of Muslim minorities in European states. Stepping back from these cases, this Article aims at a theoretical analysis of the subject, involving the contrast between value pluralism as a basis for religious freedom in international law, and other fundamental rights, i.e. women’s or children’s rights. By recognizing the intrinsic connection between individual rights and communal goods, value pluralism opens new pathways for enforcing human rights.
Keywords: Laicità e pluralismo